Nuclear reactor physics - Stacey, Weston M. (Wiley-VCH, 2018)
This third, completely revised edition of the textbook retains the proven concept of complete and balanced coverage of the topic. The first part looks at basic reactor physics, including, but not limited to nuclear reactions, diffusion theory, reactor dynamics, fuel burnup, and reactor safety.